KINERJA AUDITOR BERWAWASAN LINGKUNGAN PADA BADAN PEMERIKSA KEUANGAN SURVEI PADA AUDITOR DI LINGKUNGAN BADAN PEMERIKSA KEUANGAN JAKARTA (2017) - Dr. Hotma Napitupulu, MM.; Donny Dharmawan, MM.; Drs. Zulkarnain Moshak Zein, M.AK., CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Appositive correlation of Work motivation on environmentally sound of work productivity : A positive of healthy environment of healthy on environmentally sound of work productivity A : positive correlation of work ethic environmentally sound of work productivity